Mild Encephalitis/Encephalopathy with reversible splenial lesion syndrome: An unusual presentation of anti-GFAP astrocytopathy. (May 2020) - Oger, Valentin; Bost, Chloé; Salah, Lucie; Yazbeck, Elise; Maurey, Hélène; Bellesme, Céline; Sevin, Caroline; Adamsbaum, Catherine; Chrétien, Pascale; Benaiteau, Marie; Honnorat, Jérôme; Deiva, Kumaran
Abstract: Autoimmune glial fibrillary acidic protein (GFAP) astrocytopathy is a rare recently defined antibody-mediated encephalitis. Meningo-encephalomyelitis presentation is frequent with lymphocytic pleiocytosis in the cerebro-spinal fluid and brain MRI classically demonstrates in 50% of cases, a linear perivascular enhancement extending radially from the ventricles. Here, we describe 2 cases of pediatric autoimmune GFAP astrocytopathy with limbic encephalitis presentation and peculiar MRI characteristics: one with normal MRI and the second suggestive of Mild Encephalitis/Encephalopathy with reversible splenial lesion syndrome (MERS). These two cases illustrate that anti-GFAP antibodies should be sought in children presenting limbic encephalitis with a normal and/or MERS suggestive MRI, as treatment strategies may differ. Highlights: Anti-GFAP astrocytopathy is a rare condition in adults and children and specific MRI lesions have been suggested. Clinical outcome is good in most of the cases after immunotherapies. The pathogenicity of anti-GFAP antibodies is far from being demonstrated. Anti-GFAP antibodies should be tested for meningo-encephalitis with normal or MERS suggestive MRI, as treatment may differ.